Complete Genome Sequence Analysis of Two Divergent Groups of Sweet potato chlorotic fleck virus Isolates Collected from Korea - Hae-Ryun Kwak (The Plant Pathology Journal, 2018)
The Sweet potato chlorotic fleck virus (SPCFV), of the genus Carlavirus (family Betaflexiviridae), was first detected as one of several viruses infecting sweet potatoes (Ipomea batatas L.) in Korea. Out of 154 sweet potato samples collected in 2012 that were showing virus-like symptoms, 47 (31%) were infected with SPCFV, along with other viruses. The complete genome sequences of four SPCFV isolates were determined and analyzed using previously reported genome sequences. The complete genomes were found to contain 9,104-9,108 nucleotides, excluding the poly-A tail, containing six putative open reading frames (ORFs). Further, the SPCFV Korean isolates were divided into two groups (Group I and Group II) by phylogenetic analysis based on the complete nucleotide sequences; Group I and Group II had low nucleotide sequence identities of about 73%. For the first time, we determined the complete genome sequence for the Group II SPCFV isolates. The amino acid sequence identity in coat proteins (CP) between the two groups was over 90%, whereas the amino acid sequence identity in other proteins was less than 80%. In addition, SPCFV Korean isolates had a low amino acid sequence identity (61% CPs and 47% in the nucleotide- binding protein [NaBp] region) to that of Melon yellowing-associated virus (MYaV), a typical Carlavirus.